2006
DOI: 10.14742/ajet.1304
|View full text |Cite
|
Sign up to set email alerts
|

Gender issues in preservice teachers' training: ICT literacy and online learning

Abstract: Gender differences in self reported ICT experience and ICT literacy among first year graduate trainee teachers were investigated. Using a dynamic model, three main components of aspiring teachers' ICT literacy were covered: (1) present general problem solving and technical ICT capabilities; (2) situational and longitudinal sustainability, and (3) transferability of ICT capabilities into a future professional domain. No significant differences were found between females and males for previous experience with IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
37
4
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 33 publications
11
37
4
5
Order By: Relevance
“…This result coincided with the results of previous study (Teo, 2008a(Teo, , 2008b. This finding did agree with the past research findings which indicated significant effects of gender on computer attitudes (Margolis & Fisher, 2002;Markauskaite, 2006). For instance, Houtz and Gupta (2001) showed that both genders (males and females) had rated themselves on their ability to use the computer in significantly different ways.…”
Section: Discussionsupporting
confidence: 92%
“…This result coincided with the results of previous study (Teo, 2008a(Teo, , 2008b. This finding did agree with the past research findings which indicated significant effects of gender on computer attitudes (Margolis & Fisher, 2002;Markauskaite, 2006). For instance, Houtz and Gupta (2001) showed that both genders (males and females) had rated themselves on their ability to use the computer in significantly different ways.…”
Section: Discussionsupporting
confidence: 92%
“…1;2017 209 variable just as the literature has shown it (Rahimi & Yadollahi, 2011a, 2011bZadeh Rahim et al, 2014). However, considering non-Iranian contexts, this finding differs from the results displayed by Markauskaite (2006) and Saleh Mahdi & Sa'ad Al-Dera (2013), supporting significant role for gender in ICT usage. This divergence residing in the role of gender and CALL literacy might be accounted for through further research.…”
Section: Q2 Are Iranian Efl Teachers Literate Considering Online Intcontrasting
confidence: 82%
“…In non-Iranian contexts, the same findings could be observed. Using a dynamic model, Markauskaite (2006) examined the issue of gender and teachers' ICT literacy and reported no significant role for gender in relation to teachers' ICT literacy. Nevertheless, the counter evidence comes from an experimental study with over five hundred in-service teachers in Nigeria (Agbatogun, 2009).…”
Section: Empirical Studies On Call Literacymentioning
confidence: 99%
“…Research about teacher gender and technology use has alluded to the fact that female teachers tend to have less use of computers and/or technology in their pedagogy than their male counterparts, because of their more limited access to technology, their interest level, and their skill (Kay, 2006;Volman & van Eck, 2001;Wozney, Venkatesh, & Abrami, 2006). In a research study on technology literacy and technology experience, Markauskaite (2006) examined gender differences, and found noteworthy gender differences (in favour of the male group) in their ability to work with technology in assignments. Jamieson-Proctor, Burnett, Finger, and Watson (2006) revealed that male teachers were integrating technology into their teaching much more than the female teachers.…”
Section: Background Theoretical Perspectives On Technology Integratiomentioning
confidence: 99%